The prairie farmer ([John S. Wright, 1843)
"A leading agricultural magazine founded by the Union Agricultural Society of Chicago and a champion of farmers' rights ... Besides articles on agriculture, horticulture, and stock raising, it provided general and market news, a children's column, and departments dealing with health, household problems, and veterinary medicine." Cf. American periodicals, 1741-1900.